The Influence of Chatbot and Customer Experience on Customer Satisfaction among Generation Z Shopee Users in Bantan Village - Gunawan, Kenny; Irvan Rolyesh Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study examines the impact of chatbot technology and customer experience on customer satisfaction among Generation Z Shopee users in Bantan Village, Medan City. The research employed a quantitative approach, utilizing a sample of 150 Generation Z respondents selected through accidental sampling. Data was collected via questionnaires and analyzed using multiple linear regression analysis. The study investigated three hypotheses: the influence of chatbot on customer satisfaction, the impact of customer experience on customer satisfaction, and the combined effect of both factors. Chatbot usage showed a regression coefficient of 0.332 (p < 0.05), while customer experience demonstrated a stronger influence with a coefficient of 0.450 (p < 0.05). The combined effect of both variables explained 61.9% of the variance in customer satisfaction (R2 = 0.619). These findings suggest that e-commerce platforms should focus on optimizing their chatbot capabilities and enhancing overall customer experience to improve satisfaction levels among Generation Z users. The results indicate that both chatbot technology and customer experience have significant positive impacts on customer satisfaction.